2014
DOI: 10.3122/jabfm.2014.02.130164
|View full text |Cite
|
Sign up to set email alerts
|

How Much Shared Decision Making Occurs in Usual Primary Care of Depression?

Abstract: Background: Shared decision making (SDM) is an important component of patient-centered care, but there is little information about its use in the primary care of depression, so we sought to study its frequency in usual care as reported by patients.Methods: Telephone interview of 1168 depressed patients taking antidepressants in 88 Minnesota primary care clinics who were identified from pharmacy claims data soon after a prescription for an antidepressant. We measured depression severity with the 9-item Patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
1
41
1
2
Order By: Relevance
“…Los resultados indicaron que las personas de mayor edad y que llevaban más tiempo en tratamiento psiquiátrico mostraron preferir un rol más pasivo en la toma de decisiones, mientras que las de mayor nivel de estudios preferían ser más activas. En este sentido, diferentes estudios detectan que las personas mayores y las que llevan largos períodos en tratamiento informan de menor tasa de toma de decisión compartida (Proctor, Hasche, Morrow-Howell, Shumway, & Snell, 2008;Schneider et al, 2006;Solberg et al, 2014).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados indicaron que las personas de mayor edad y que llevaban más tiempo en tratamiento psiquiátrico mostraron preferir un rol más pasivo en la toma de decisiones, mientras que las de mayor nivel de estudios preferían ser más activas. En este sentido, diferentes estudios detectan que las personas mayores y las que llevan largos períodos en tratamiento informan de menor tasa de toma de decisión compartida (Proctor, Hasche, Morrow-Howell, Shumway, & Snell, 2008;Schneider et al, 2006;Solberg et al, 2014).…”
Section: Discussionunclassified
“…Se ha encontrado que aunque mujeres y hombres no se diferencian en preferencias, las mujeres asumen un papel más pasivo que los hombres. Del mismo modo, las personas de más edad y menor nivel educativo han mostrado implicarse en menor medida en la toma de decisión, mostrando estilos más pasivos o paternalistas (Schneider et al, 2006;Singh et al, 2010).…”
Section: Introductionunclassified
“…Another improvement would be the use of a clear theoretical framework for sharing power and responsibility that links dimensions of patient safety with specific outcomes. Older patients with depression and those who had been treated for a longer period reported far less shared decision making [42]. A study by Holm et al [30] evaluating healthcare team members' perceptions of their role in encouraging patients to participate in shared decision-making revealed the importance of preventing the violation of human dignity based on changing understanding and attitudes, increasing patients' autonomy and clarifying the team coordinator's role and responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be involved in decisions about their situation and/or treatment and the healthcare services need to be redesigned in order to support self-management. Shared decision making is an important component of a patient-centred care [42]. However, the question of whether patient-centred care leads to better outcomes needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Approaching a large number of patients who filled a new prescription for an antidepressant, Solberg et al 3 considered the amount of patient-reported SDM in many practices in Minnesota. Half of the patients identified were excluded: 20% because they reported that their prescription was not for depression, and a quarter because their score on the 9-item Patient Health Questionnaire was not high enough to meet study criteria at the time of the data collection.…”
mentioning
confidence: 99%